Stretch influence on pre-competitive stress on juvenile soccer players - P.V. Rogatto; K.J. Curiacos; J.A. Leme; R.A. Barberi (Desafio Singular, 2008)
Soccer show a series of stress-generated situations. The streatching may contribut to decrease this stress negative effects. The pre-competitive moment is stress generator. Yhe objetive of this study was to verify the effects of strectch on pre-competitive stress in soccer players. To this, 17 juvenile soccer players were allocated into two groups: control group (CG) and strecth group (SG). All participants responsed to TEF (Stress soccer test) and GA stretching during 30 minutes while GC not realized any physical activity. After this, both groups responded to TEF and was inverted in the next game. The situations "sleep badly on previous night" and "Be damaged for arbitrator" was avaliated with more negative reponses while " Himself charged to win" and " The adversary is the favourite" was was avaliated with more positive reponses. SG showed positive avaliations increased copared to CG, decreased on nule response and decreased on -1 and -3 responses. GC showed decrease in -2 responses. Concluded that pre-competitive situation modify negatively the athletes avaliation while the strecth interfere positively in front the avaliation of stressor situations in juvenile players.